A minimal computational model for three-dimensional cell migration. Issue 161 (24th December 2019) - Cao, Yuansheng; Ghabache, Elisabeth; Miao, Yuchuan; Niman, Cassandra; Hakozaki, Hiroyuki; Reck-Peterson, Samara L.; Devreotes, Peter N.; Rappel, Wouter-Jan
Abstract : During migration, eukaryotic cells can continuously change their three-dimensional morphology, resulting in a highly dynamic and complex process. Further complicating this process is the observation that the same cell type can rapidly switch between different modes of migration. Modelling this complexity necessitates models that are able to track deforming membranes and that can capture the intracellular dynamics responsible for changes in migration modes. Here we develop an efficient three-dimensional computational model for cell migration, which couples cell mechanics to a simple intracellular activator–inhibitor signalling system. We compare the computational results to quantitative experiments using the social amoeba Dictyostelium discoideum . The model can reproduce the observed migration modes generated by varying either mechanical or biochemical model parameters and suggests a coupling between the substrate and the biomechanics of the cell.